Analysis and Design of an Web-Based Ticketing Service Helpdesk at Food and Packaging Machinery Company - Jansen Wiratama; Fenina Adline Twince Tobing (Universitas Multimedia Nusantara, 2022)
PT Putra Chandra Sentosa is a company engaged in food and packaging machinery. In the business process that runs in the customer service division, the process of recording service submissions by customer service is carried out using word processing software which has the potential for data accumulation and the search for information on service submissions to be slower. Customer service has difficulty dividing technicians' duties due to service status updates that are not real-time, and they have to wait for technicians to submit a letter of assignment after the visit. In addition to using conventional data processing, customers who complain about service results or technician attitudes make management feel they need feedback reports regarding customer satisfaction. This study aims to design a website that is useful to facilitate the search for service information, perform a balanced division of technician tasks and assist management in seeing customer satisfaction in the form of reports. The Helpdesk Ticketing website in this study has been developed using Website Development Life Cycle (WDLC) model with the Hypertext Preprocessor (PHP) programming language, Unified Modeling Language (UML) notation and MySQL database. The PHP programming language is used in this research because various operating systems can run it via a browser. This research produces a Helpdesk Ticketing website that can answer the needs of the company PT Putra Chandra Sentosa. This research also proves that the website can optimize business processes in recording service submissions compared to using word processing software